Overview of zoonotic diseases in peri-urban areas and introduction to the special issue - Divya Aggarwal; Sumant Swain; B S Singh; Sanjiv Kumar (Wolters Kluwer Medknow Publications, 2020)
Emerging zoonoses are the product of socio economic and anthropogenic environmental changes. As human societies continue to develop, pathogens from animal hosts have continued to spill over into our population However, Peri-urban ecosystems remain neglected in the country. With a subsequent increase in demand for food, there has been an expansion of formal and informal livestock-based food production sectors in these areas. The increasing close contact between animals and humans in both work and living environments creates hot spots in peri-urban areas, thereby increasing vulnerability to zoonotic disease transmission and other health hazards associated with food safety, water, and sanitation-related diseases. This paper explores the efforts made by different research bodies to reduce the prevalence of zoonotic diseases in peri-urban areas.